An Ethnopharmaceutical Study on the Hypolipidemic Formulae in Taiwan Issued by Traditional Chinese Medicine Pharmacies - Min-Han Chi; Jung Chao; Chien-Yu Ko; Shyh-Shyun Huang; Shyh-Shyun Huang (Frontiers Media S.A., 2022)
Globally, approximately one-third of ischemic heart diseases are due to hyperlipidemia, which has been shown to cause various metabolic disorders. This study was aimed to disassemble and analyze hypolipidemic formulae sold by traditional Chinese medicine (TCM) pharmacies. Using commonly used statistical parameters in ethnopharmacology, we identified the core drug combination of the hypolipidemic formulae, thereby exploring the strategy by which the Taiwanese people select hypolipidemic drugs. Most important of all, we preserved the inherited knowledge of TCM. We visited 116 TCM pharmacies in Taiwan and collected 91 TCM formulae. The formulae were mainly disassembled by macroscopical identification, and the medicinal materials with a relative frequency of citation (RFC) >0.2 were defined as commonly used medicinal materials. Subsequently, we sorted the information of medicinal materials recorded in the Pharmacopeia, searched for modern pharmacological research on commonly used medicinal materials using PubMed database, and visualized data based on the statistical results. Finally, the core hypolipidemic medicinal materials used in folk medicine were obtained. Of the 91 TCM formulae collected in this study, 80 traditional Chinese medicinal materials were used, belonging to 43 families, predominantly Lamiaceae. Roots were the most commonly used part as a medicinal material. There were 17 commonly used medicinal materials. Based on medicinal records in Pharmacopeia, most flavors and properties were warm and pungent, the majority traditional effects were "tonifying and replenishing" and "blood-regulating." Besides, the targeted diseases searching from modern pharmacological studies were diabetes mellitus and dyslipidemia. The core medicinal materials consisted of Astragalus mongholicus Bunge and Crataegus pinnatifida Bunge, and the core formulae were Bu-Yang-Huan-Wu-Tang and Xie-Fu-Zhu-Yu-Tang. In addition, 7 groups of folk misused medicinal materials were found. Although these TCMs have been used for a long period of time, their hypolipidemic mechanisms remain unclear, and further studies are needed to validate their safety and efficacy.